Synthesis, Molecular Characterization, and Antibacterial Testing of Silver–Cadmium Bimetallic Bionanoparticles Prepared from the Sidaguri (Sida rhombifolia L.) Extract - Mandey, Fredryk; Rangga Bua, Anita Rahelea; Rahayu, Ismi Sri; Permatasari, Nur Umriani (UI Scholars Hub, 2025)
Herein, we successfully synthesized, characterized, and examined the antibacterial activity of silver–cadmium bimetallic bionanoparticles prepared by mixing the aqueous extract of Sidaguri (Sida rhombifolia L.) and mixtures of silver nitrate and cadmium nitrate (yield = 0.2035 g). Ultraviolet–visible spectroscopy, Fourier transforms infrared spectroscopy, X-ray diffraction, scanning electron microscopy–energy dispersive X-ray spectroscopy, and particle-size analysis, revealed that the products exhibited a maximum absorption wavelength of 427.5 nm with an absorbance intensity of 0.790; a face centered cubic structure; Ag and Cd mass percentages of 98.52% and 1.28%, respectively; an average molecular diameter of 43.8 nm, and a polydispersity index of 0.573. The bimetallic nanoparticles were tested as an antibacterial agent against Staphylococcus aureus and Escherichia coli. They exhibited inhibition zone diameters of 9.2 and 10 mm for E. coli and S. aureus, respectively.